PERTUMBUHAN DAN PERKEMBANGAN TUNAS KULTUR EMBRIO CARYOTA NO BECC. - Hoesen, Djadja Siti Hazar (Research Center for Biology-Indonesian Institute of Sciences, 1997)
Caryota no Becc,(fish-tailpalm) is considered vulnerable palm, Its population is declining from the habitat by destructive exploitation but also to some extent by local people who remove the edible apex or 'cabbage 'as a vegetable and also obtain sago from the pith of the trunk,so kill the tree.A though its biological characteristics have not been fully studied,this species is also potentially for ornamental plant Thus conservation measures should be taken to improve the status of this threatened species. Tissue culture techniques may provide ways either to propagate or to conserve itin-vitro. Naturally Caryota no Becc.palm fruit after 20years and they can germinate more than 3 months after sowing with low germination value.In this experiment,the tissue culture response of this species are studied using the explant of embryo from (relatively) young fruit (juvenility fruit).The effect ofBA and 2,4D on the shoot growth, root growth and calluses was evaluated, while the evaluation of the effect ofactifated charcoal was discussed. The satisfactory results have not been achieved.